Strengthening international patient advocacy perspectives on patient involvement in HTA within the HTAi Patient and Citizen Involvement Interest Group – Commentary. Issue 1 (December 2017) - Wale, Janet; Scott, Anna; Bertelsen, Neil; Meade, Nick
Plain Language Summary Health Technology Assessment (HTA) is an evidence-based decision-making process, focusing on evaluating health technologies for funding within a healthcare system. 'Health technologies' include medications, medical devices, diagnostics, medical procedures and services. Health Technology Assessment international (HTAi) is a global society for those who produce, use, participate in, or encounter HTA. The HTAi Secretariat supports special interest groups within HTAi. One such special interest group, the Patient and Citizen Involvement in HTA Interest Group (PCIG), focuses on strengthening patient involvement in HTA. PCIG's members are from HTA agencies, research, industry, and patient organisations. We describe the steps PCIG has taken to form an international panel of patient advocates (the Patient Panel) as an autonomous group within its governance structure that reports directly to the PCIG Steering Committee. The Patient Panel was established in order to strengthen meaningful patient involvement in HTA by working co-productively with other PCIG members to develop resources accessible to patient organisations. Patient advocates known to be active within HTA in their own countries were invited to form the inaugural group, with one person appointed to chair the group for the first year. Documentation had been prepared to inform potential members and set out potential roles as seen by the Steering Committee. The appointed Patient Panel is defining its own terms of reference, goals and objectives. The Panel Chair is a member of the PCIG Steering Committee, and is mentored by the retiring PCIG chair. A registry of activities is part of monitoring and evaluation. Abstract Background Health Technology Assessment (HTA) is an evidence-based decision-making process, focusing on evaluating health technologies for funding within a healthcare system or medical insurance system. 'Health technologies' are understood broadly, and include medications, medical devices, diagnostics, medical procedures and services. Health Technology Assessment international (HTAi) is a global society for those who produce, use, participate in, or encounter HTA. The HTAi Secretariat supports special interest groups within HTAi, including the Patient and Citizen Involvement in HTA Interest Group (PCIG), which focuses on strengthening patient involvement in HTA. PCIG's members come from HTA agencies, research, industry, and patient organisations. Main body We describe the steps the PCIG has taken to form an international panel of patient advocates as an autonomous group within its governance structure, reporting directly to the PCIG Steering Committee. Patient advocates known to be active within HTA in their own countries were invited to form the inaugural group. One person was invited to chair the Panel for the first year of its operation, based on the candidate's experience of working across diseases and countries, and being new to HTAi. Documentation was prepared to inform potential members of the Panel and set out potential roles as seen by the Steering Committee. The Panel came into being in March 2016 and is now setting out its own working principles, goals and objectives. The Panel Chair is a member of the PCIG Steering Committee, and is mentored by the previous PCIG chair. A registry of activities has been set up as part of monitoring and evaluation. The Patient Panel is intended to provide a focus within the PCIG for patient advocates to work among themselves and co-productively through the PCIG Working Groups to develop mutual understanding and strengthen meaningful patient involvement in HTA internationally. Patient advocates can benefit from a clear understanding the evidence requirements within HTA and how information can be effectively presented by patient groups to decision-making bodies. Conclusion The HTAi Patient and Citizen Involvement Interest Group has set up a Patient Panel consisting of patient advocates. The intent is to work co-productively to advance patient involvement in HTA.